Decreased Proliferation in the Neurogenic Niche, Disorganized Neuroblast Migration, and Increased Oligodendrogenesis in Adult Netrin-5-Deficient Mice - Ikegaya, Shunsuke; Iga, Yurika; Mikawa, Sumiko; Zhou, Li; Abe, Manabu; Sakimura, Kenji; Sato, Kohji; Yamagishi, Satoru (Frontiers in Neuroscience, 2020)
In the adult mouse brain, neurogenesis mainly occurs in the ventricular-subventricular zone (V-SVZ) and the subgranular zone of the hippocampal dentate gyrus. Neuroblasts generated in the V-SVZ migrate to the olfactory bulb via the rostral migratory stream in response to guidance molecules, such as netrin-1. We previously showed that the related netrin-5 (NTN5) is expressed in Mash1-positive transit-amplifying cells and doublecortin-positive neuroblasts in the granule cell layer of the olfactory bulb, the rostral migratory stream, and the subgranular zone of the adult mouse brain. However, the precise role of NTN5 in adult neurogenesis has not been investigated. In this study, we show that neurogenic proliferation is impaired in NTN5 knockout mice. The number of proliferated (EdU-labeled) cells in the NTN5 KO mice was significantly lower in the V-SVZ, whereas the number of Ki67-positive proliferating cells were unchanged, suggesting that longer cell cycle and decreased cell division in NTN5 KO mice. The number of EdU-labeled cells in the rostral migratory stream (RMS) and olfactory bulb were unchanged. By contrast, the number of EdU-labeled cells in the cortex, basal ganglia/lateral septal nucleus, and corpus callosum/anterior commissure was increased, which largely represented oligodendrocyte lineage cells. Lastly, we found that the chain-migration in the RMS of NTN5 KO mice was disorganized. These findings suggest that NTN5 may play important roles in promoting neurogenic proliferation in the V-SVZ, organizing proper chain-migration in the RMS and suppressing oligodendrogenesis in the brain.